Association of the Type of Public Pension With Mental Health Among South Korean Older Adults: Longitudinal Observational Study - Seung Hoon Kim; Hyunkyu Kim; Sung Hoon Jeong; Eun-Cheol Park (JMIR Publications, 2024)
BackgroundAs income and health are closely related, retirement is considered undesirable for health. Many studies have shown the association between pension and health, but no research has considered the association between contribution-based public pensions or their types and health. ObjectiveThis study investigates the association between the type of contributory public pension and depressive symptoms among older adults. MethodsWe analyzed the data of 4541 older adults who participated in the South Korea Welfare Panel Study (2014-2020). Depressive symptoms were measured using the 11-item Center for Epidemiologic Studies Depression scale. Public pensions in South Korea are classified into specific corporate pensions and national pensions. For subgroup analyses, pensioners were categorized according to the amount of pension received and the proportion of public pension over gross income. Analyses using generalized estimating equations were conducted for longitudinal data. ResultsIndividuals receiving public pension, regardless of the pension type, demonstrated significantly decreased depressive symptoms (national pension: β=-.734; P<.001; specific corporate pension: β=-.775; P=.02). For both pension types, the higher the amount of benefits, the lower were the depression scores. However, this association was absent for those who received the smaller amount among the specific corporate pensioners. In low-income households, the decrease in the depressive symptoms based on the amount of public pension benefits was greater (fourth quartile of national pension: β=-1.472; P<.001; second and third quartiles of specific corporate pension: β=-3.646; P<.001). ConclusionsOur study shows that contributory public pension is significantly associated with lower depressive symptoms, and this association is prominent in low-income households. Thus, contributory public pensions may be good income sources for improving the mental health of older adults after retirement.